POTENSI EKSTRAK KULIT BUAH DELIMA TERHADAP PERTUMBUHAN Candida albicans SECARA IN VITRO - jirna inyoman (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
AbstractBackground: Infection by the Candida albicans has increased globally and reported fungal resistance to synthetic antifungal. It is, therefore, necessary to develop effective antifungal medicines for the treatment of infection by Candida albicans. This study aims to determine the content of phytochemical and inhibitory power of pomegranate skin extract on Candida albicans growth. Methode: This research type is the true experiment with post test only control design. The method used for the phytochemical test is qualitative tube method. Pomegranate skin resistivity test on Candida albicans growth was done by disc diffusion method. The pomegranate skin is tested at concentrations of 100%, 75%, 50%, 25% and 10%. Negative control with 96% alcohol and positive control using ketocenazole 2%. Result: The results of phytochemical tests showed pomegranate skin extract containing saponins, tannins, and flavonoids. Pomegranate skin extracts are not able to inhibit the growth of Candida albicans by disc diffusion method.Conclusion:The conclusion of this study is pomegranate skin extracts can not inhibit Candida albicans growth, For other researchers which use jatropha curcas twigs, are suggested to do a phytochemical test quantitatively and to test the antifungal potential with liquid DMSO 10%, kloroform and petroleum eter..Keywords:Potential antifungal, pomegranate skin extract, Candida albicans